Adenosine Receptors in Developing and Adult Mouse Neuromuscular Junctions and Functional Links With Other Metabotropic Receptor Pathways - Tomàs, Josep; Garcia, Neus; Lanuza, Maria A.; Santafé, Manel M.; Tomàs, Marta; Nadal, Laura; Hurtado, Erica; Simó-Ollé, Anna; Cilleros-Mañé, Víctor; Just-Borràs, Laia (Frontiers in Pharmacology, 2018)
In the last few years, we have studied the presence and involvement in synaptogenesis and mature transmitter release of the adenosine autoreceptors (AR) in the mammalian neuromuscular junction (NMJ). Here, we review and bring together the previously published data to emphasize the relevance of these receptors for developmental axonal competition, synaptic loss and mature NMJ functional modulation. However, in addition to AR, activity-dependent mediators originating from any of the three cells that make the synapse (nerve, muscle and glial cells) cross the extracellular cleft to generate signals in target metabotropic receptors. Thus, the integrated interpretation of the complementary function of all these receptors is needed. We previously studied, in the NMJ, the links of AR with mAChR and the neurotrophin receptor TrkB in the control of synapse elimination and transmitter release. We conclude that AR cooperate with these receptors through synergistic and antagonistic effects in the developmental synapse elimination process. In the adult NMJ, this cooperation is manifested so as that the functional integrity of a given receptor group depends on the other receptors operating normally (i.e. the functional integrity of mAChR depends on AR operating normally). These observations underlie the relevance of AR in the NMJ function.